2018
DOI: 10.1136/jech-2017-209776
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and public health: an analysis of the regulatory approach to assessing the carcinogenicity of glyphosate in the European Union

Abstract: The present paper scrutinises the European authorities’ assessment of the carcinogenic hazard posed by glyphosate based on Regulation (EC) 1272/2008. We use the authorities’ own criteria as a benchmark to analyse their weight of evidence (WoE) approach. Therefore, our analysis goes beyond the comparison of the assessments made by the European Food Safety Authority and the International Agency for Research on Cancer published by others. We show that not classifying glyphosate as a carcinogen by the European aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
0
13
0
2
Order By: Relevance
“…Besides their ability to kill insects, they have been reported to inactivate acetylcholinesterase in humans causing the accumulation of the acetylcholine, resulting in convulsions, seizures, and even death (Costa, 2006;Gupta, 2004;Liu et al, 2013). The carcinogenicity and genotoxicity of pesticides are thoroughly studied by various researchers (Clausing, Robinson, & Burtscher-Schaden, 2018;Cocco, 2018;Devillers, Mombelli, & Samsera, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Besides their ability to kill insects, they have been reported to inactivate acetylcholinesterase in humans causing the accumulation of the acetylcholine, resulting in convulsions, seizures, and even death (Costa, 2006;Gupta, 2004;Liu et al, 2013). The carcinogenicity and genotoxicity of pesticides are thoroughly studied by various researchers (Clausing, Robinson, & Burtscher-Schaden, 2018;Cocco, 2018;Devillers, Mombelli, & Samsera, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate has also been indicated as a significant water pollutant from intensive agriculture in Mexico (Ruiz-Toledo et al, 2014). The concentrations of glyphosate in surface waters in the EU appears to be lower, but consistently occurring e.g., Germany (Skark et al, 1998), the Mediterranean (Barceló and Hennion, 1997), the Northern region Lode, 2001, 2002;Kjaer et al, 2005), in France (Botta et al, 2009;Van Stempvoort et al, 2016;Clausing et al, 2018) and elsewhere, and its dissipation has been found to be slowed down in formulation and in the presence of algal biofilms (Klátyik et al, 2017b). Thus, glyphosate residues have been deemed to be worldwide the most common pesticide contaminant in freshwater ecosystems, AMPA being the most frequent, glyphosate being the third most frequent contaminant in France (Villeneuve et al, 2011).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…Indeed, the EFSA opinion does not cite any peer reviewed studies (European Food Safety Authority, 2015a). As a follow-up, a recent evaluation publication condemns the BfR, EFSA, and ECHA of violating current risk assessment guidelines, when dismissing 11 statistically significant cases of increased tumor incidences in two rat and five mouse studies, and claims that glyphosate should have been classified in the EU category 1B, "presumed human carcinogen" (Clausing et al, 2018). EFSA, in the meantime, published its guidance document on uncertainty analysis (Benford et al, 2018) that considers possible omission of carcinogenicity data on the basis of genotoxicity/carcinogenicity margins of exposure, differences in the benchmark dose level due to unquantified uncertainties, the relevance and adverseness of the effects seen animals to humans, or misinterpretation of the probability of a given chemical having a carcinogenic mode of action as the probability cancer caused in an individual.…”
Section: Efsa Vs Iarcmentioning
confidence: 99%
“…However, BfR and EFSA opined five reasons for dismissing these carcinogenic effects, using a “weight of evidence” (WOE) approach. Clausing and Clausing et al, however, have adequately challenged the validity of the BfR and EFSA approach, and their five WOE reasons for dismissing evidence of carcinogenicity.…”
mentioning
confidence: 99%